Hadronic contributions to the anomalous magnetic moment of the muon - Göcke, Tobias; Justus Liebig University Giessen (My University, 2012)
The anomalous magnetic moment if the muon is an observable that receives quantum corrections from all three interactions of the Standard Model. The experimental and theoretical determinations seem to disagree thus opening the possibility to look for new physics beyond the Standard Model. The deviation is, however, only marginally larger than the uncertainties for both experiment and theory. On the theoretical side the uncertainty is dominated by contributions from the strong interactions. Therefore we consider the two most relevant hadronic contributions to the muon anomaly. In particular we calculate the hadronic vacuum polarisation (HVP) and the hadronic light-by-light(HLBL) scattering diagrams using the method of Dyson-Schwinger equations. We show that we reproduce HVP on the less-ten-percent level compared to model independent determinations. Our ongoing efforts for the much more complicated HLBL contribution show that the existing model calculations have underestimated their error. In particular we find that Green´s function that have a realistic momentum dependence and tensor structure have to be taken into account for such a calculations. We explain and exemplify why we think that the Dyson-Schwinger approach is able to achieve a HLBL prediction that is on a similar level of accuracy as the HVP result that we present.

Das anomale magnetische Moment des Myons ist eine Observable, welche sensitiv auf alle drei Wechselwirkungen des Standardmodells ist. Die experimentell und theoretisch mit hoher Genauigkeit bestimmten Werte weichen allerdings voneinander ab, was interessante Spekulationen ueber Physik jenseits des Standardmodells moeglich macht. Da die Abweichung allerdings von der selben Groessenordnung ist, wie die entsprechenden Unsicherheiten, ist eine noch praezisere Kenntnis von experimentellen und theoretischen Ergebnissen unumgaenglich. Auf der theoretischen Seite sind es die Beitraege der starken Wechselwirkung, die den Fehler dominieren. Deshalb beschaeftigen wir uns in dieser Arbeit die beiden relevanstesten hadronischen Beitraege, die hadronische Vakuumpolarisation (HVP) und die hadronische Light-Light-Streunung (HLBL). Wir zeigen, dass mit der Methode der Dyson-Schwinger Gleichungen eine Beschreibung der HVP gegeben ist, die weniger zehn Prozent von modellunabhaengigen Verfahren abweicht. Unsere Arbeit bezueglich des deutlich anspruchsvolleren HLBL Beitrages zeigen, dass die Fehlerabschaetzungen, welche in Modellrechnungen gemacht worden sind, wohl zu optimistisch waren. Wir finden, dass Green´s-Funktionen mit realistischer Impulsabhaengigkeit und Tensorstruktur notwendige Ingredienzien fuer eine zuverlaessige Beschreibung von HLBL sind. Wir argumentieren und veranschaulichen warum wir der Meinung sind, dass die Dyson-Schwinger Methode fuer HLBL ultimativ eine aehnliche Praezision erreichen kann wie im Fall von HVP.
Keywords: Myon; anomales magnetisches Moment; hadronisch; Licht-Licht-Streunung; Dyson-Schwinger; muon; anomalous magnetic moment; hadronic; light-by-light; Dyson-Schwinger; ddc:530